(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
The purpose of this research was to identify the organizational processes of absorptive capacity that support the development of dynamic capacities in adverse environments in a case of the alcoholic beverages sector in Venezuela. The epistemological assumption selected was the interpretive paradigm and qualitative research using the descriptive case study as a method. The main results showed that the organizational processes of absorption capacity were related to quick decisions; Strategic Alliances; product design based on economic conditions and changes in demand; anticipation of changes; attainable and measurable goals; human resources policy: retain your staff; and maintain the quality of its products. It is concluded that in adverse environments, companies develop absorption capacities to meet the limitations derived from adversity; volatility; uncertainty; and hostility; and despite this, they create possibilities to survive and grow. This research broadens the context of application of dynamic capabilities.